Contested Landscapes: Land Grabbing, Customary Rights, and Environmental Degradation in Eastern Indonesia - Akhmad Syafi’i; Sherina Prahitaningtyas; Muhammad Saied (International Journal of Social Research, 2026)
This study explores the contested dynamics of land grabbing, customary land rights, and environmental degradation in Eastern Indonesia, with a case study focused on Merauke Regency, Papua Province. Utilizing a qualitative political ecology approach, the research combines in-depth interviews, employee questionnaires, field observations, and document analysis to examine how corporate concessions intersect with indigenous territories. The findings reveal systemic exclusion of indigenous communities in land acquisition processes, characterized by weak consultation, disregard for customary tenure, and the erosion of traditional livelihoods. Although companies assert legal compliance, the affected communities report significant loss of access to sacred lands, environmental decline, and cultural displacement. Notably, 90% of plantation workers surveyed recognized the negative impact on indigenous livelihoods, while only 25% believed local communities were included in decision-making. These results highlight the political nature of environmental change and demonstrate how land commodification undermines ecological integrity and indigenous sovereignty. The study contributes to political ecology discourse by documenting spatial injustice and calling for policy reforms that recognize customary land rights and support inclusive development.